Observasi Pelaksanaan Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran Guru di UPT SDN 05 Sungayang (Indo-MathEdu Intellectuals Journal, 2026)
Academic supervision is one of the principal's essential functions in improving teacher professionalism and the quality of learning. This study aims to describe the implementation of academic supervision by the principal in enhancing the quality of teachers' learning processes at UPT SDN 05 Sungayang. The study employed a descriptive qualitative approach using an observational method. Data were collected through observations, interviews, and documentation involving the principal and teachers. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that academic supervision was carried out through classroom observations, review of teaching documents, individual coaching, and feedback sessions for teachers. The principal also implemented motivational strategies through rewards and educational guidance. Follow-up activities included discussions, training programs, and mentoring to improve teachers' competencies. The effectiveness of academic supervision was influenced by teachers' motivation, principal support, effective communication, and the availability of educational facilities and infrastructure. Overall, the implementation of academic supervision at UPT SDN 05 Sungayang contributed positively to improving the quality of learning and teacher professionalism